Potential targets for the hepatitis C virus-mediated autoimmune thyroiditis - Andrade, Luis Jesuino Oliveira; Oliveira, Luisa Correia Matos de; Oliveira, Gabriela Correia Matos de (Medicina (Ribeirao Preto), 2021)
Introduction: The mechanisms by which hepatitis C virus (HCV) infection induces autoimmune thyroiditis (AIT) have been studied, and it was suggested that inflammatory cytokines during HCV infection would change the thyroperoxidase (TPO) signaling cascade and thyroglobulin (Tg) determining autoimmune thyroid disease.Objective: To show the signaling pathway, of TPO and Tg, and their potential targets mediated HCV in individuals with hepatitis C.Methods: The mapping of the signaling pathway was based on a review study approach and performed using the automatic annotation server of the Kyoto and Genome Encyclopedia (KEGG). PathVisio is free software for analysis and design of open source routes, and was used for the graphic representation of the signaling pathway.Results: The contigs were extracted from the KEGG database and their mapped transcription represents the signaling pathway of the main biomolecules that triggers the AIT. The action of HCV, or its treatment can trigger AIT that is characterized by the presence of autoantibodies against TPO and Tg. In AIT, autoreactive CD4 + T lymphocytes recruit B cells and CD8 + T cells in the thyroid. The progression of the disease leads to the death of thyroid cellsand hypothyroidism.Conclusion: HCV or its treatment activates several signaling pathways with thyroid cells damage resulting in AIT and secondary hypothyroidism to cellular apoptosis.